(untitled) (Al-Qamar, 2022)
The problem of “Royat-e-Hilal" of Ramadan and Shawwal is not of recent years rather this problem has been keep arising on these sacred occasions since last sixty years. According to geographical point of view, Pakistan is situated on such a part of Earth where seeing of moon on two different dates can absolutely be refused. Bhutto Govt in 1974 ,after the decline of Ayub Khan,passed a law from National Assembly to solve this issue for ever. Bhutto’s Govt has declared to set up a "Royat-e-Hilal" Committee on govt level which will comprise of one central and four zonal committees which exists till today. These committees too could not eliminate the difference on the issue of "Royat-e-Hilal" and didn’t pay any effective role. Now the issue along with the Govt has become more a religious and regional. So there is a need of presenting this issue before public on scientific and Islamic basis. I would try to research on this topic on scientific and religious basis in my article.